Corporate bonds, asset-backed securities and deferred checks in Argentina - Alejandro Bedoya; Roque Fernández; Celeste González; Sergio Pernice; Jorge M. Streb (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2007)
We describe the evolution of three types of corporate securities in Argentina, namely, corporate bonds, asset-backed securities and deferred checks. Corporate bonds (obligaciones negociables) were legally authorized in 1988, and after a tax reform in 1991 they became an important financing vehicle. Asset backed securities (fideicomisos), legally created in 1995, have been issued since 1996. They typically bundle together small credits of a similar category. Deferred checks (cheques de pago diferido) exist since 1993, alongside standard checks. They can be negotiated on the exchange since 2003, and are akin to commercial paper. Corporate bonds have been overwhelmingly issued by large firms and banks, with an average issue size of 53 million dollars. Asset backed securities have an average value of 9 million dollars. Deferred checks are typically used by smaller firms, and those traded on the exchange of the Buenos Aires board of trade have an average value of 9 thousand dollars.
Keywords: G3; 330; private securities; corporate bonds; asset-backed securities; deferred checks; Unternehmensfinanzierung; Argentinien